Now I can see: How brand interactions influence channel loyalty and purchase intention in optical physical stores - Bilro, R. G.; Dias, F. (Management Research: The Journal of the Iberoamerican Academy of Management, 2022)
Purpose – This study aims to analyse the effect of brand interactions such as personal interaction, problem-solving, reliability and store physical appearance on channel loyalty and purchase intention in optical physical stores. Design/methodology/approach – The hypotheses are tested through quantitative research based on a questionnaire with a sample of 414 respondents. Researchers conduct multiple regressions to analyse the data. Findings – The findings reveal that channel loyalty and purchase intention are positively influenced differently. Person-to-person interactions play a vital role in both constructs (dependent variables). This study also offers relevant managerial implications and future research avenues. Originality/value – Despite the relevance of purchase intention in the literature, almost no studies have been published about the intention to buy glasses in the optical physical stores, a relevant contribution this paper offers to the literature. The finding that the store’s physical aspect did not prove to be influential for channel loyalty is also an innovative and relevant contribution of this research.